Developments in the flow of complex fluids in tubes - Siginer, Dennis A. (Springer International Publishing, 2015)
This book is dedicated to the tube flow of viscoelastic fluids and Newtonian single and multi-phase particle-laden fluids. This succinct volume collects the most recent analytical developments and experimental findings, in particular in predicting the secondary field, highlighting the historical developments which led to the progress made. This book brings a fresh and unique perspective and covers and interprets efforts to model laminar flow of viscoelastic fluids in tubes and laminar and turbulent flow of single and multi-phase particle-laden flow of linear fluids in light of the latest findings. This book also: Presents a thorough account of successes and failures in modeling and predicting tube flow of viscoelastic fluids and concentrated particle-laden flow of Newtonian fluids with specific explanations throughout Emphasizes the most up-to-date challenges in the field without requiring the reader to wade through detailed treatment of various theories Bridges the latest research results and established knowledge from the archival literature